Estudo da interação entre alumínio e os constituintes de formulações de eritropoetina empregando HPLC e AAS - Santos, Marlei Veiga dos (2009)
Erythropoietin (EPO) is a glycoprotein which stimulates the erythropoiesis (production of hemaceas) and is clinically used for the treatment of renal anemia. EPO formulations present usually elevated contamination by aluminum. Aluminum is known to participate in the pathogenesis of osteodystrophy and encephalopathy associated with chronic hemodialysis, and has been proposed to be involved in central nervous system degeneration diseases such as Alzheimer s diseases. In the present work, the presence of Al as contaminant in erythropoietin formulations consumed by chronic renal patients, was investigated by developing and optimizing a chromatographic method for separation and determination of proteins, with subsequent collection of fractions and measured of the Al present by graphite furnace atomic absorption spectrometry (GF AAS). As the commercialization of pharmaceutical forms of EPO are in glass containers with rubber cap (bottle, vial or syringe), it was investigated the ability of the constituents of EPO formulations (salts, amino acids, urea, and mannitol among others) to promote the extraction of aluminum present in both glass and rubber. The tests were performed considering the process of sterilization and the contact of the solutions during storage. The results demonstrated that the interaction of EPO with aluminum is higher than that of albumin (the other proteic constituent). Among the other constituents, citric acid and citrate presented the highest interaction. For each constituent there is probably a different mechanism for the release of aluminum from glass and rubber, but all constituent of EPO formulations interacted with glass and rubber packaging, leading to their contamination by aluminum. As the level of contamination by aluminum in commercial formulations of erythropoietin was determined, and it was observed that the lyophilized powder presented the lowest contamination by aluminum, this form must be the choice for renal patients, due to the susceptibility of these patients to aluminum toxicity.